The Sovereignty Aspect on Earth (Arctic, Antarctic, Seabed and Ocean Floor) and on Moon: Comparative Study - Sena, Ketut Andri; Wisanjaya, I Gede Pasek Eka (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2019)
The increased attempts to utilize moon has emerged issue relating to its sovereign status. This research attempts to compare sovereignty aspect on earth (Arctic, Antarctic, seabed) and on moon, by applying normative legal research. On Earth, several states have claimed their territories upon the Arctic and the Antarctic. However, those claims remain unresolved, and in any event, the Arctic and the Antarctic territories are still open for public. On the other hand, seabed and ocean floor have been regulated by international legal instruments that no sovereignty may be claimed upon. On Moon, several treaties and declarations have governed that no sovereignty may be claimed upon, and that any activity there must be for the peaceful purpose of mankind. Subsequently, the Arctic, Antarctic, seabed and ocean floor, and also moon have been declared as common heritage of mankind.